2018
DOI: 10.1016/j.surg.2018.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary concepts in hernia prevention: Selected proceedings from the 2017 International Symposium on Prevention of Incisional Hernias

Abstract: Incisional hernia is a frequent complication of midline laparotomy and enterostomal creation and is associated with high morbidity, decreased quality of life, and high costs. The International Symposium on Incisional Hernia Prevention was held October 19-20, 2017, at the InterContinental Hotel in San Francisco, CA, hosted by the Department of Surgery, University of California, San Francisco. One hundred and three attendees included general and plastic surgeons from 9 countries, including principal participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Mesh placement is a simple surgical method that may prevent wound/fascial dehiscence and incisional hernias . However, the efficacy of preventive mesh implantation in organ transplant recipients has not been well studied; only case reports and case series investigating pediatric KTx and including less than 10 patients have been published so far .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesh placement is a simple surgical method that may prevent wound/fascial dehiscence and incisional hernias . However, the efficacy of preventive mesh implantation in organ transplant recipients has not been well studied; only case reports and case series investigating pediatric KTx and including less than 10 patients have been published so far .…”
Section: Discussionmentioning
confidence: 99%
“…Mesh placement is a simple surgical method that may prevent wound/fascial dehiscence and incisional hernias. 13,14,[24][25][26][27][28][29] However, the efficacy of preventive mesh implantation in organ transplant recipients has not been well studied; only case reports and case series investigating pediatric KTx and including less than 10 patients have been published so far. 15,30,31 To address this, we investigated a retrospective cohort to compare post-KTx wound complications between patients receiving preventive mesh reinforcement (Vicryl ® mesh) and no-mesh controls.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that ''choice of suture size appears to only significantly affect suture retention if the difference in suture diameter is greater than or equal to 0.1 mm.'' NEW OPTIONS FOR FASCIAL CLOSURE TO DECREASE HERNIA RECURRENCE Minimal strides have been made in the laparotomy or hernia repair field along with a failure rate of suture repairs of incisional hernias of 63% at 10 years [26] and perhaps explained by a reliance on the standard suture design for tissue approximation. Translating concepts of the biology and physics involved at the STI has propagated a need for new, more reliable types of abdominal wall closure.…”
Section: Suture Sizementioning
confidence: 99%
“…Hernia prevention can come in many forms, including patient prehabilitation, optimal suture technique, and mesh reinforced closures. Patient Prehabilitation including control of diabetes, smoking cessation, weight loss, and good overall nutritional status, although in emergency surgery this is not possible [3]. The prevention of IH is important because of its high complication rate and whilst repair is possible recurrence rates are high, 32% with mesh repair.…”
Section: Introductionmentioning
confidence: 99%
“…So far there is no ideal method to identify patients at high risk of developing IH, this variety in the criteria of inclusion of patients in different studies makes is very complicate to compare the results. Therefore, in the case of attempts to prevent incisional hernia formation, preoperative risk stratification and decision algorithms will be of potentially important value [3]. Recently, several investigators identified a multitude of risk factors and created risk models for predicting IH after surgery.…”
Section: Introductionmentioning
confidence: 99%